Peran Musyawarah Guru Mata Pelajaran (Mgmp) Untuk Meningkatkan Kompetensi Profesional Guru PAI: Studi Kasus MGMP PAI SMP Negeri Kabupaten Kediri - Husna, Farihatul (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2016)
The study is intended to examine the role of MGMP PAI of Junior Highschools in Kediri regency in increasing the material mastery of PAI, inincreasing the ability to develop the materials for PAI, as well as developingthe ability to use information and communication technology in learningPAI. The research used a qualitative descriptive approach in the form ofcase study. Data collection techniques used were observation, interviews,and documentation. Results of the research revealed that the role ofMGMP PAI of Junior High schools in Kediri regency are done throughconsidering PAI materials of junior high schools, organizing workshop, aswell as analyzing PAI textbook. In addition, the ability to develop teachingmaterials is done through Scientific Writing (KTI), Classroom ActionResearch (PTK), and collegial supervision of teachers. Finally, the abilityto use Information and Communication Technology (ICT) of PAI teachersthrough ICT is done through training and facilitation of teachers in theform of self-development. Practically, MGMP is important to improve theprofessional competence of PAI teachers.